Acoustic characteristics of phonation in “wet voice” conditions - Murugappan, Shanmugam (Acoustical Society of America, 2010)
A perceptible change in phonation characteristics after a swallow has long been considered evidence that food and∕or drink material has entered the laryngeal vestibule and is on the surface of the vocal folds as they vibrate. The current paper investigates the acoustic characteristics of phonation when liquid material is present on the vocal folds, using ex vivo porcine larynges as a model. Consistent with instrumental examinations of swallowing disorders or dysphagia in humans, three liquids of different Varibar viscosity (“thin liquid,” “nectar,” and “honey”) were studied at constant volume. The presence of materials on the folds during phonation was generally found to suppress the higher frequency harmonics and generate intermittent additional frequencies in the low and high end of the acoustic spectrum. Perturbation measures showed a higher percentage of jitter and shimmer when liquid material was present on the folds during phonation, but they were unable to differentiate statistically between the three fluid conditions. The finite correlation dimension and positive Lyapunov exponent measures indicated that the presence of materials on the vocal folds excited a chaotic system. Further, these measures were able to reliably differentiate between the baseline and different types of liquid on the vocal folds.